Project Report on Astute Corporate Service Limited (2022-24) Under the Guidance of Prof. Vipul Pancholi - Tidke, Ruchita Yogesh (ATLAS SkillTech University, 2024)
In an increasingly digital world where information exchange is an integral part of our daily lives, the importance of document verification has grown immensely. Document verification is the process of authenticating and validating the legitimacy of various forms of documentation, including identity cards, passports, academic certificates, business contracts, and many others. It serves as a crucial safeguard against fraud, forgery, and identity theft, providing assurance to individuals, organizations, and governments that the information they rely upon is genuine and trustworthy.
Project Report on Astute Corporate Service Limited (2022-24) Under the Guidance of Prof. Vipul Pancholi